New paradigm in the economic literature on global warming - Miguel Cuerdo-Mir; Raquel Ibar-Alonso (Heliyon, 2023)
This study examines how international agreements (especially the 1992 Rio Summit, the 1997 Kyoto Protocol, and the 2015 Paris Agreement) on climate change have fueled rampant economic literature worldwide. However, it has not been systematically classified or distinguished from the more traditional studies in this field. Hence, we use a scientometric analysis using four different approaches: natural language processing (NLP), citation analysis, co-citation network analysis, and content analysis. We conduct an ambitious Boolean search of 30 terms in Scopus and use NLP, along with unsupervised statistical learning techniques and content analysis to classify and analyze 2400 of the most relevant studies in this field. As such, independent results are complementary. We provide novel literature by mapping four major clusters: climate change corporate, climate finance, climate capitalism, and climate gateway belief.